Rules and rands: credit legislation and developmental credit to micro and small enterprises in South Africa - Madalane, Zokwanda (Graduate School of Business (GSB), 2022)
The role played by Micro and Small Enterprises in many economies globally is huge and important. It is even more significant for economies in Africa such as South Africa where there are high levels of poverty and unemployment. In South Africa, Micro and Small Enterprises can contribute towards addressing the challenge of poverty and unemployment, given their proven history of job creation. However, their contribution is constrained by the lack of access to credit for growth, which is a result of a deficit of credit information among other contributing factors. This inhibits their growth. In South Africa, developmental credit was introduced through the National Credit Act 34 of 2005 to improve access to credit for low-income earners, including Micro and Small Enterprises. This type of credit is different from other types of credit because it bypasses the challenge of credit information, allowing the credit application of Micro and Small Enterprises to be assessed without the use of credit information (credit history). However, since the introduction of the Act, there has been little uptake and granting of developmental credit. This dissertation aimed to determine the reasons for this. This dissertation uses a qualitative research approach. Interviews were conducted with Micro and Small Enterprises and questionnaires administered with developmental Credit Providers, and the National Credit Regulator. Therefore, qualitative information from the above credit market stakeholders was analysed to get to the findings. The findings of this research are three-fold. In respect of credit providers, findings show that, despite the legislative provisions, there is still the use of credit information by large financial institutions, which adversely affects access to developmental credit. Findings for Micro and Small Enterprises reveal that there is a lack of knowledge of this type of credit. This is affected by the fact that Micro and Small Enterprises perceive credit as being difficult to access because of the use of credit information, which they lack, and therefore do not explore various types of credit available and suitable for their businesses. Furthermore, there are only a few credit providers, which provide developmental credit in the country; this affects their footprint in the country and different provinces. Lastly, the findings on legislation are that the requirements to register as a developmental credit provider limit the number of credit providers, which can register to provide developmental credit.